The large, diverse, and robust arsenal of Ralstonia solanacearum type III effectors and their in planta functions. (8th August 2020) - Landry, David; González‐Fuente, Manuel; Deslandes, Laurent; Peeters, Nemo
Abstract: The type III secretion system with its delivered type III effectors (T3Es) is one of the main virulence determinants of Ralstonia solanacearum, a worldwide devastating plant pathogenic bacterium affecting many crop species. The pan‐effectome of the R. solanacearum species complex has been exhaustively identified and is composed of more than 100 different T3Es. Among the reported strains, their content ranges from 45 to 76 T3Es. This considerably large and varied effectome could be considered one of the factors contributing to the wide host range of R. solanacearum . In order to understand how R. solanacearum uses its T3Es to subvert the host cellular processes, many functional studies have been conducted over the last three decades. It has been shown that R. solanacearum effectors, as those from other plant pathogens, can suppress plant defence mechanisms, modulate the host metabolism, or avoid bacterial recognition through a wide variety of molecular mechanisms. R. solanacearum T3Es can also be perceived by the plant and trigger immune responses. To date, the molecular mechanisms employed by R. solanacearum T3Es to modulate these host processes have been described for a growing number of T3Es, although they remain unknown for the majority of them. In this microreview, we summarize and discuss the current knowledge on the characterized R. solanacearum species complex T3Es. Abstract : This review compiles all the current functional knowledge on the large and diverse repertoire of type III effectors from bacteria belonging to the Ralstonia solanacearum species complex.